해수파울링이 판형 열교환기 성능에 미치는 실험적 연구 - 백원근(Won Keun Baik); 허재혁(Jaehyeok Heo); 윤린(Rin Yun) (설비공학 논문집, 30(5), 2018)
Two plate type heat exchangers were tested. One was under fouling conditions from seawater and the other was under clean condition. Overall heat coefficient, heat transfer coefficient, fouling thermal resistance, and pressure drop of the heat exchangers were obtained. Effects of fouling on plate type heat exchangers were then investigated. The test heat exchanger, a differential pressure transducer, and two mass flow meters were installed. The working fluid used in the experiment was water on the seawater side and brine on the other side of the heat exchanger. Operational temperatures for seawater side were 10℃, 20℃, and 30℃. The brine side temperatures were 5℃, 15℃, and 25℃. Operational flow rates at both sides were 20-30 lpm. The overall heat transfer coefficient for seawater side was increased by an average of 21% in clean condition without fouling. Pressure drop was less than 2 kPa with temperature variation. However, pressure drop for seawater side was increased four times under fouling conditions. KCI Citation Count: 2